Natural dyes and eco-print techniques elevate the art of nature and local culture - Irwan Syah Bin Md Yusoff, Irwan Syah; Zulhelmy Hamdan, Zulhelmy; Azhari Md Hashim, Azhari; Mohamad Fakrol Zaini, Mohamad Fakrol; Mohd Anuar, Amer Syazwan (Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2024)
This study investigates using natural dyes and eco-print techniques as innovative methods for enhancing artistic expression while preserving local culture and promoting environmental sustainability. Natural dyes, derived from plant, mineral, and organic sources, present an eco-friendly alternative to synthetic dyes traditionally employed in textile production. The eco-print technique, which involves transferring natural pigments from flora onto fabric, exemplifies a harmonious blend of art and ecology. Through qualitative research methods and case studies of successful eco- printing initiatives, this study highlights these techniques' cultural significance, aesthetic value, and environmental implications. The findings suggest that integrating natural dyes and eco-printing preserves traditional craftsmanship and fosters a sense of community identity and environmental consciousness. This research contributes to the growing discourse on sustainable fashion, demonstrating how the revival of these techniques can elevate the appreciation of local cultural heritage through ecological artistry.